Granzymes in health and diseases: the good, the bad and the ugly - Cigalotto, Lavinia; Martinvalet, Denis (Frontiers in Immunology, 2024)
Granzymes are a family of serine proteases, composed of five human members: GA, B, H, M and K. They were first discovered in the 1980s within cytotoxic granules released during NK cell- and T cell-mediated killing. Through their various proteolytic activities, granzymes can trigger different pathways within cells, all of which ultimately lead to the same result, cell death. Over the years, the initial consideration of granzymes as mere cytotoxic mediators has changed due to surprising findings demonstrating their expression in cells other than immune effectors as well as new intracellular and extracellular activities. Additional roles have been identified in the extracellular milieu, following granzyme escape from the immunological synapse or their release by specific cell types. Outside the cell, granzyme activities mediate extracellular matrix alteration via the degradation of matrix proteins or surface receptors. In certain contexts, these processes are essential for tissue homeostasis; in others, excessive matrix degradation and extensive cell death contribute to the onset of chronic diseases, inflammation, and autoimmunity. Here, we provide an overview of both the physiological and pathological roles of granzymes, highlighting their utility while also recognizing how their unregulated presence can trigger the development and/or worsening of diseases.